Searchingfor Optimum Service Rate In a Queuing System - N.N.Elkhadar,; M.M.Mekaeil, (Scientific Journal of University of Benghazi, 2026)
The use of queuing theory in practice involves two major aspects: 1. Selection of the appropriate mathematical model that will represent the real system adequately with the objective of determining the systems measures of performance. 2. Implementation of a decision model based on the systems measures of performance for the purpose of designing the service facility. This work is merely a simulation study using a celebrated simulation programs in operations research namely TORA, LINGO, LINDO, Process Model plus EXCEL. In this study we invstigated the optimal service rate in the queueing system (M/M/1): (GD/∞/∞), plus finding the optimal service rate for a given arrival rate several service rates are tried to obtain the performance measurements which are important in determining the minimal cost by using the cost function TC(μ) = Cu + CWLS. S Promising results are obtained which are consistent with all the theoretical results available in the literature concerning the steady state behavior of a queueing system.